Three-dimensional carbon-loaded copper nano material and preparation method thereof, and two-dimensional carbon nanosheet-loaded copper nano particle material and preparation method thereof

By calcining ZnCu-BTC with trivalent iron source and acidification treatment, three-dimensional carbon-loaded cubic copper nanospecies and two-dimensional carbon nanosheet-loaded copper nanoparticles materials are formed, which solves the problem of morphology regulation of copper nanoparticles in the existing technology and realizes the The efficient application of materials is in the fields of electrochemical energy storage and catalysis.

CN119259044APending Publication Date: 2025-01-07WENCHENG CHANGTAI ELECTRIC POWER CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411369796.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing ZnCu-BTC nanomaterials are difficult to accurately regulate the morphological transformation of copper nanoparticles, especially the cube-shaped copper nanoparticles, which have not been reported, affecting the catalytic efficiency and performance.

Method used

By mixing ZnCu-BTC with trivalent iron source to calcinate, temperature and time are controlled to form a three-dimensional carbon-supported copper nanospecies material, and a two-dimensional carbon nanosheet-supported copper nanoparticles material is obtained through acidification treatment, and the copper nanoparticles have a cubic structure.

Benefits of technology

The cubic structure of copper nano species is loaded on three-dimensional carbon materials, improving the morphological uniformity and performance of the materials, and is suitable for electrochemical energy storage, catalysis and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259044A_ABST
    Figure CN119259044A_ABST
Patent Text Reader

Abstract

The invention provides a three-dimensional carbon-loaded copper nano-material and a preparation method thereof, and a two-dimensional carbon nanosheet-loaded copper nano-particle material and a preparation method thereof, and belongs to the technical field of porous micro-nano materials. The three-dimensional carbon loaded copper nano species material provided by the invention comprises three-dimensional carbon and copper nano species loaded on the three-dimensional carbon, the copper nano species comprise zero-valent copper and bivalent copper; the copper nanospecies are of a cubic structure. The invention also provides a preparation method of the three-dimensional carbon-loaded copper nano material, which comprises the following steps: mixing ZnCu-BTC with a ferric iron source, and calcining to obtain the three-dimensional carbon-loaded copper nano material. The copper nano species in the obtained three-dimensional carbon-loaded copper nano species material are of a cubic structure and are uniform in morphology; according to the provided method, by means of the competitive coordination principle of ligands, the morphology of the nano-particles is accurately controlled by controlling the dosage of the ferric iron source, and the copper nano-species of a cubic structure is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of porous micro-nano materials, and specifically relates to a three-dimensional carbon-loaded copper nano-species material and a preparation method thereof, and a two-dimensional carbon nanosheet-loaded copper nano-particle material and a preparation method thereof. Background Art

[0002] As one of the metal organic framework (MOF) materials, ZnCu-BTC has the characteristics of a three-dimensional open framework and high stability, high specific surface area, large porosity, excellent thermal stability and structural regulation ability at different scales. It is one of the most widely studied MOFs. Due to its structural characteristics and physicochemical properties, ZnCu-BTC nanomaterials can be widely used in electrochemical energy storage, catalysis, adsorption, separation and gas storage.

[0003] By regulating the morphology of copper nanoparticles in ZnCu-BTC nanomaterials, nanomaterials with different morphologies can be obtained, and the specific surface area, exposed crystal planes and surface defects of the materials can be changed, thereby affecting the catalytic efficiency and performance. However, current research still cannot accurately regulate the morphology of nanoparticles, and there is no report on cubic copper nanoparticles. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a three-dimensional carbon-supported copper nanospecies material and a preparation method thereof, a two-dimensional carbon nanosheet-supported copper nanoparticle material and a preparation method thereof. The three-dimensional carbon-supported copper nanospecies material provided by the present invention has a uniform morphology, and the copper nanospecies presents a cubic structure.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The invention provides a three-dimensional carbon-loaded copper nano-species material, comprising three-dimensional carbon and copper nano-species loaded on the three-dimensional carbon; the copper nano-species comprises zero-valent copper and divalent copper; and the copper nano-species presents a cubic structure.

[0007] The present invention also provides a method for preparing the three-dimensional carbon-supported copper nanospecies material described in the above technical solution, comprising the following steps:

[0008] Mixing ZnCu-BTC with a trivalent iron source and calcining to obtain the three-dimensional carbon-supported copper nanospecies material;

[0009] The mass ratio of the ZnCu-BTC to the ferric iron source is 10:3-5;

[0010] The calcination temperature is 900-1000°C.

[0011] Preferably, the ferric iron source includes one or more of ferric chloride, ferric nitrate and ferric sulfate.

[0012] Preferably, the calcination is carried out in an inert atmosphere;

[0013] The calcination time is 2 to 4 hours.

[0014] Preferably, the preparation method of ZnCu-BTC comprises: mixing a zinc source, a copper source, trimesic acid and a polar organic solvent, and performing a solvothermal reaction to obtain ZnCu-BTC;

[0015] The mass ratio of the zinc source to the copper source is 1:1;

[0016] The mass ratio of the copper source to trimesic acid is 2:3.

[0017] Preferably, the zinc source includes one or more of zinc chloride, zinc sulfate and zinc nitrate;

[0018] The copper source includes one or more of copper chloride, copper sulfate and copper nitrate.

[0019] Preferably, the polar organic solvent is N,N-dimethylformamide;

[0020] The mass ratio of the copper source to the volume of the polar organic solvent is 4 mg:1-2 mL.

[0021] The present invention provides a two-dimensional carbon nanosheet-loaded copper nanoparticle material, comprising a two-dimensional carbon nanosheet and copper nanoparticles loaded on the two-dimensional carbon nanosheet; the copper nanoparticles comprise CuCl nanoparticles and zero-valent copper nanoparticles; and the copper nanoparticles are of a cubic structure.

[0022] Preferably, the particle size of the copper nanoparticles is 100-200 nm.

[0023] The present invention also provides a method for preparing the two-dimensional carbon nanosheet-loaded copper nanoparticle material described in the above technical solution, comprising the following steps: acidifying the three-dimensional carbon-loaded copper nanospecies material to obtain the two-dimensional carbon nanosheet-loaded copper nanoparticle material;

[0024] The acid solution used for the acidification is a hydrochloric acid solution;

[0025] The concentration of the hydrochloric acid solution is 6M.

[0026] The present invention provides a three-dimensional carbon-loaded copper nano-species material, comprising three-dimensional carbon and copper nano-species loaded on the three-dimensional carbon; the copper nano-species comprises zero-valent copper and divalent copper; the copper nano-species is in a cubic structure. The present invention is the first to load cubic copper nano-species on three-dimensional carbon, which can be applied to the fields of electrochemical energy storage, catalysis, adsorption, etc.

[0027] The present invention provides a method for preparing the above-mentioned three-dimensional carbon-loaded copper nano-species material, using a ZnCu-based MOF material ZnCu-BTC, utilizing a competitive coordination method of a ligand, and by adding a trivalent iron source and controlling the dosage, a balance is achieved between the morphology control and composition selection of the material, thereby obtaining a copper nano-species with a cubic structure loaded on a three-dimensional carbon material.

[0028] The present invention also provides a two-dimensional carbon nanosheet-loaded copper nanoparticle material and a preparation method thereof, wherein acidification is performed on the basis of a three-dimensional carbon-loaded copper nanoparticle material, and the three-dimensional carbon material is peeled off to obtain a two-dimensional sheet carbon nanomaterial, and the copper nanoparticles exposed after peeling undergo a disproportionation reaction under acidic conditions to obtain CuCl nanoparticles. The preparation method provided by the present invention is low in cost, simple in operation, safe in reaction, short in time, and highly repeatable. The method is expected to achieve universality and be extended to the preparation of other composite materials, and the obtained two-dimensional carbon nanosheet-loaded copper nanoparticle material (CuCl-CNS) can be applied to many scenarios.

[0029] The test results show that the two-dimensional carbon nanosheets loaded with copper nanoparticles obtained by the method provided by the present invention have a particle size of 100 to 200 nm. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0031] Figure 1 A schematic diagram of the preparation of the two-dimensional carbon nanosheet-loaded copper nanoparticle material provided by the present invention;

[0032] Figure 2 This is a schematic diagram of the preparation of the nanomaterial obtained in Comparative Example 1;

[0033] Figure 3 This is a SEM image of the MOF material ZnCu-BTC prepared in Example 1;

[0034] Figure 4 This is a SEM image of the carbon material prepared in Comparative Example 1;

[0035] Figure 5 This is a SEM image of the two-dimensional carbon nanosheet-loaded copper nanoparticle material prepared in Example 1;

[0036] Figure 6 TEM image of the two-dimensional carbon nanosheet-loaded copper nanoparticle material prepared in Example 1;

[0037] Figure 7 XRD patterns of the nanomaterials prepared for ZnCu-BTC, Comparative Example 1 and Example 1;

[0038] Figure 8 XPS graphs of the nanomaterials prepared in Comparative Example 1 and Example 1. DETAILED DESCRIPTION

[0039] The invention provides a three-dimensional carbon-loaded copper nano-species material, comprising three-dimensional carbon and copper nano-species loaded on the three-dimensional carbon; the copper nano-species comprises zero-valent copper and divalent copper; and the copper nano-species presents a cubic structure.

[0040] In the present invention, the size of the three-dimensional carbon is preferably 1 to 3 μm.

[0041] The present invention also provides a method for preparing the three-dimensional carbon-supported copper nanospecies material described in the above technical solution, comprising the following steps:

[0042] Mixing ZnCu-BTC with a trivalent iron source and calcining to obtain the three-dimensional carbon-supported copper nanospecies material;

[0043] The mass ratio of the ZnCu-BTC to the ferric iron source is 10:3-5;

[0044] The calcination temperature is 900-1000°C.

[0045] In the present invention, unless otherwise specified, the raw materials and equipment involved are commercially available products well known in the art.

[0046] In the present invention, the preparation method of ZnCu-BTC preferably comprises: mixing a zinc source, a copper source, trimesic acid and a polar organic solvent, and performing a solvothermal reaction to obtain ZnCu-BTC;

[0047] The mass ratio of the zinc source to the copper source is 1:1;

[0048] The mass ratio of the copper source to trimesic acid is 2:3.

[0049] In the present invention, the zinc source preferably includes one or more of zinc chloride, zinc sulfate and zinc nitrate, more preferably zinc chloride and / or zinc nitrate, and further preferably zinc nitrate.

[0050] In the present invention, the copper source preferably includes one or more of copper chloride, copper sulfate and copper nitrate, more preferably copper chloride and / or copper nitrate, and further preferably copper nitrate.

[0051] In the present invention, the polar organic solvent is preferably N,N-dimethylformamide (DMF); the mass ratio of the copper source to the volume ratio of the polar organic solvent is preferably 4 mg:1-2 mL. In a specific embodiment, the mass ratio of the copper source to the volume ratio of the polar organic solvent can be 4 mg:1 mL or 4 mg:2 mL.

[0052] The present invention has no special requirements on the method of mixing the zinc source, the copper source, trimesic acid and the polar organic solvent, and the commonly used technical means in the art can be used.

[0053] In the present invention, the temperature of the solvothermal reaction is preferably 80-90°C. In a specific embodiment, the temperature of the solvothermal reaction may be 80°C, 85°C or 90°C. The time of the solvothermal reaction is preferably 22-26h. In a specific embodiment, the time of the solvothermal reaction may be 22h, 24h or 26h.

[0054] In the present invention, after the solvothermal reaction, the obtained product liquid is preferably subjected to solid-liquid separation and solid washing.

[0055] The present invention has no special requirements on the method of solid-liquid separation, and the commonly used technical means in the art can be used. In a specific embodiment of the present invention, centrifugation is used for solid-liquid separation.

[0056] In the present invention, the washing is preferably performed using ethanol and DMF, and the number of washing is preferably 3 to 4 times.

[0057] The invention obtains a regular octahedral ZnCu-BTC material by specifically limiting the mass ratio of a zinc source to a copper source, and a copper source to trimesic acid.

[0058] After obtaining the ZnCu-BTC material, the present invention mixes the ZnCu-BTC with a trivalent iron source and calcines the mixture to obtain the carbon-supported cubic copper nanoparticle material.

[0059] In the present invention, the ferric iron source preferably includes one or more of ferric chloride, ferric nitrate and ferric sulfate, more preferably ferric chloride and / or ferric nitrate, and further preferably ferric chloride. In the present invention, the ferric chloride is preferably FeCl3·6H2O. The present invention mixes ZnCu-BTC with a ferric iron source, specifically limits the amount of the two, utilizes the competitive coordination principle of ligands, and strikes a balance between the morphological control and composition selection of the material, thereby obtaining a copper nano-species with a cubic structure loaded on a three-dimensional carbon material.

[0060] The present invention preferably utilizes a grinding method to mix the ZnCu-BTC with a ferric iron source, and the grinding time is preferably 10 to 15 minutes. In a specific embodiment, the grinding time can be 10 minutes, 12 minutes, 14 minutes or 15 minutes.

[0061] In the present invention, the calcination temperature is 900-1000°C. In a specific embodiment, the calcination temperature can be 900°C, 950°C or 1000°C; the calcination time is preferably 2-4h. In a specific embodiment, the calcination time can be 2h, 3h or 4h. Since the boiling point of Zn is 907°C, calcination at this temperature can convert Zn from solid to gas, thereby removing Zn. The present invention carbonizes MOF to form a carbon material by calcination. At the same time, the copper in the MOF material after calcination is converted into zero-valent copper. The zero-valent copper will compete with the trivalent iron in the ligand, and the copper will change from zero-valent to divalent, and the iron will change from trivalent to divalent. At the same time, the crystal is deconstructed and the copper species reprecipitated after calcination are cubic. The present invention introduces a small amount of iron species into the three-dimensional carbon-loaded copper nanospecies material, but the mass of the iron species is too small and can be ignored.

[0062] In the present invention, the heating rate to reach the calcination temperature is preferably 10° C. / min. In the present invention, the calcination is preferably carried out in an inert atmosphere, and the inert gas is preferably argon.

[0063] The present invention provides a two-dimensional carbon nanosheet-loaded copper nanoparticle material, comprising a two-dimensional carbon nanosheet and copper nanoparticles loaded on the two-dimensional carbon nanosheet; the copper nanoparticles comprise CuCl nanoparticles and zero-valent copper nanoparticles; and the copper nanoparticles are of a cubic structure.

[0064] In the present invention, the particle size of the copper nanoparticles is preferably 100-200 nm.

[0065] The present invention also provides a method for preparing the two-dimensional carbon nanosheet-loaded copper nanoparticle material described in the above technical solution, wherein the three-dimensional carbon-loaded copper nanospecies material is acidified to obtain the two-dimensional carbon nanosheet-loaded copper nanoparticle material;

[0066] The acid solution used for the acidification is a hydrochloric acid solution;

[0067] The concentration of the hydrochloric acid solution is 6M.

[0068] In the present invention, the amount of the hydrochloric acid solution is preferably sufficient to completely immerse the three-dimensional carbon-loaded copper nanospecies material. In the present invention, the acidification time is preferably 1 to 3 hours. In a specific embodiment, the acidification time can be 1 hour, 2 hours or 3 hours. The present invention peels off the three-dimensional carbon material by acidification to obtain a two-dimensional carbon nanosheet material, while exposing more zero-valent copper nanospecies. The surface of the newly exposed zero-valent copper nanoparticles will change from zero valent to positive divalent in an acidic environment. During the acidification process, the divalent copper on the surface of the copper nanoparticles and the zero-valent copper inside the copper nanoparticles exchange electrons at the junction to obtain CuCl nanoparticles. At the same time, there is also zero-valent copper on the surface of the two-dimensional carbon nanosheet material that does not participate in the reaction.

[0069] In the present invention, the acidification preferably further comprises washing the solid product after acidification. In the present invention, the washing is preferably performed using ethanol, and the number of washings is preferably 3 to 4 times.

[0070] The preparation process of the two-dimensional carbon nanosheet-loaded copper nanoparticle material provided by the present invention is as follows: Figure 1 shown.

[0071] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described in conjunction with specific embodiments below. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Any modification, equivalent replacement, improvement, etc. made to the implementation methods of the present invention based on the technical essence and general principles of the present invention without creative work should be within the scope of protection of the present invention.

[0072] Example 1

[0073] Mix 20 mg Zn(NO3)2·6H2O, 20 mg Cu(NO3)2·3H2O, 30 mg trimesic acid (H3BTC) and 5 mL N,N-dimethylformamide (DMF), place it in an oven at 85°C and heat it at a constant temperature for 24 h. After cooling to room temperature, centrifuge it, wash it with DMF and ethanol three times, and obtain a light blue powder MOF material recorded as ZnCu-BTC.

[0074] 100 mg ZnCu-BTC and 40 mg FeCl3·6H2O were mixed and ground for 15 min to obtain a light green mixture powder. The mixture was placed on a quartz boat, heated to 900 °C at a heating rate of 10 °C / min, calcined in argon for 3 h, and cooled to room temperature to obtain a three-dimensional carbon-supported copper nanospecies material. The three-dimensional carbon-supported copper nanospecies material was soaked in 6M hydrochloric acid for 2 h, washed three times with ethanol, and dried to obtain a two-dimensional carbon nanosheet-supported copper nanoparticle material, recorded as CuCl-CNS.

[0075] Comparative Example 1

[0076] The ZnCu-BTC prepared in Example 1 was placed on a quartz boat, heated to 900°C at a heating rate of 10°C / min, calcined in argon for 3 hours, and cooled to room temperature to obtain a three-dimensional carbon composite material, recorded as ZnCu-BTC-C, with a yield of 40%.

[0077] The schematic diagram of the preparation process of the three-dimensional carbon composite material obtained in Comparative Example 1 is as follows Figure 2 shown.

[0078] Comparative Example 2

[0079] 100 mg ZnCu-BTC and 80 mg FeCl3·6H2O were mixed and ground, and calcined, and other conditions were the same as those in Example 1. A two-dimensional carbon nanosheet-loaded copper nanoparticle material was obtained. After electron microscopy observation, no cubic copper nanoparticles were obtained.

[0080] Scanning the ZnCu-BTC material under an electron microscope revealed Figure 3 .from Figure 3 It can be seen that the micron-sized ZnCu-BTC presents a cubic and octahedral shape.

[0081] The three-dimensional carbon composite material obtained in Comparative Example 1 was scanned by electron microscope to obtain Figure 4 . Figure 4 It shows that after direct calcination of ZnCu-BTC material, a three-dimensional carbon composite material ZnCu-BTC-C loaded with round copper nanoparticles is obtained.

[0082] Figure 5 This is a SEM image of the two-dimensional carbon nanosheet-loaded copper nanoparticle material prepared in Example 1. Figure 5 The two-dimensional carbon nanosheets loaded with copper nanoparticles were obtained by calcining ZnCu-BTC material with iron salt and then acidifying. The copper nanoparticles were cubic in shape with a particle size of 100 to 200 nm.

[0083] Figure 6 This is a TEM image of the two-dimensional carbon nanosheet-loaded copper nanoparticle material prepared in Example 1. Figure 6 It is demonstrated that CuCl-CNS is a two-dimensional carbon nanosheet structure loaded with cubic copper nanoparticles.

[0084] Figure 7 XRD diagrams of the nanomaterials prepared in ZnCu-BTC, Comparative Example 1 and Example 1. Figure 7 The middle left figure shows the actual XRD pattern of ZnCu-BTC (upper) and the simulated XRD pattern (lower). Figure 7As shown in the left figure, the ZnCu-BTC material has good crystallinity, and the calcined ZnCu-BTC-C has obvious characteristic peaks of metallic copper. Figure 7 As can be seen from the right figure, ZnCu-BTC was calcined and then acidified after being fully ground with FeCl3 to generate CuCl nanocubes, showing the characteristic peaks of Cu, CuCl and FeO.

[0085] Figure 8 XPS graphs of the nanomaterials prepared in Comparative Example 1 and Example 1. Figure 8 It is shown in the figure that Cu, C and O elements are present in both pyrolysis products (including ZnCu-BTC-C and CuCl-CNS). It is worth noting that the chloride content in CuCl-CNS is significantly increased after the in situ formation of CuCl nanocrystals. In the Cu 2p fine spectrum of CuCl-CNS, the two peaks at 932.6eV and 952.4eV correspond to Cu(0), and the two peaks at 934.5eV and 954.6eV correspond to Cu(Ⅰ) / Cu(Ⅱ).

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A three-dimensional carbon-supported copper nanospecies material, characterized in that: The invention comprises three-dimensional carbon and copper nano-species loaded on the three-dimensional carbon; the copper nano-species comprises zero-valent copper and divalent copper; and the copper nano-species presents a cubic structure.

2. The method for preparing the three-dimensional carbon-supported copper nanospecies material according to claim 1, characterized in that: The following steps are involved: Mixing ZnCu-BTC with a trivalent iron source and calcining to obtain the three-dimensional carbon-supported copper nanospecies material; The mass ratio of the ZnCu-BTC to the ferric iron source is 10:3-5; The calcination temperature is 900-1000°C.

3. The preparation method according to claim 2, characterized in that: The ferric iron source includes one or more of ferric chloride, ferric nitrate and ferric sulfate.

4. The preparation method according to claim 2 or 3, characterized in that: The calcination is carried out in an inert atmosphere; The calcination time is 2 to 4 hours.

5. The preparation method according to claim 2, characterized in that: The preparation method of ZnCu-BTC comprises: mixing a zinc source, a copper source, trimesic acid and a polar organic solvent, and performing a solvothermal reaction to obtain ZnCu-BTC; The mass ratio of the zinc source to the copper source is 1:1; The mass ratio of the copper source to trimesic acid is 2:

3.

6. The preparation method according to claim 5, characterized in that: The zinc source includes one or more of zinc chloride, zinc sulfate and zinc nitrate; The copper source includes one or more of copper chloride, copper sulfate and copper nitrate.

7. The preparation method according to claim 5, characterized in that: The polar organic solvent is N,N-dimethylformamide; The mass ratio of the copper source to the volume of the polar organic solvent is 4 mg:1-2 mL.

8. A two-dimensional carbon nanosheet-loaded copper nanoparticle material, characterized in that: It comprises two-dimensional carbon nanosheets and copper nanoparticles loaded on the two-dimensional carbon nanosheets; the copper nanoparticles comprise CuCl nanoparticles and zero-valent copper nanoparticles; and the copper nanoparticles are of cubic structure.

9. The two-dimensional carbon nanosheet-loaded copper nanoparticle material according to claim 8, characterized in that: The particle size of the copper nanoparticles is 100-200 nm.

10. The method for preparing the two-dimensional carbon nanosheet-loaded copper nanoparticle material according to any one of claims 8 to 9, characterized in that: The method comprises the following steps: acidifying the three-dimensional carbon-supported copper nano-species material according to claim 1 or any one of claims 2 to 7 to obtain the two-dimensional carbon nanosheet-supported copper nano-particle material; The acid solution used for the acidification is a hydrochloric acid solution; The concentration of the hydrochloric acid solution is 6M.